Surgical Management of Stage IIIA Non-Small Cell Lung Cancer - Van Schil, Paul E.; Berzenji, Lawek; Yogeswaran, Suresh K.; Hendriks, Jeroen M.; Lauwers, Patrick (Frontiers in Oncology, 2017)
According to the 8th edition of the Tumor – Node – Metastasis (TNM) classification stage III non-small cell lung cancer is subdivided into stages IIIA, IIIB and IIIC. They represent a heterogeneous group of bronchogenic carcinomas with locoregional involvement by extension of the primary tumor and/or ipsilateral or contralateral lymph node involvement. Surgical indications have not been definitely established but in general, long-term survival is only obtained in those patients in whom a complete resection is obtained. This mini-review mainly focusses on stage IIIA disease comprising patients with locoregionally advanced lung cancers. Different subcategories of N2 involvement exist, which range from unexpected N2 disease after thorough preoperative staging or “surprise” N2, to bulky N2 involvement, mostly treated by chemoradiation, and finally, the intermediate category of potentially resectable N2 disease treated with a combined modality regimen. After induction therapy for preoperative N2 involvement, best surgical results are obtained with proven mediastinal downstaging when a lobectomy is feasible to obtain a microscopic complete resection. However, no definite, universally accepted guidelines exist. A relatively new entity is salvage surgery applied for recurrent disease after full-dose chemoradiation when no other therapeutic options exist. Equally, only a small subset of patients with T4N0-1 disease qualify for surgical resection after thorough discussion within a multidisciplinary tumor board on the condition that a complete resection is feasible. Targeted therapies and immunotherapy have recently become part of our therapeutic armamentarium and it might be expected that they will be incorporated in current regimens after careful evaluation in randomized clinical trials.